Failure behaviors of anisotropic shale with a circular cavity subjected to uniaxial compression - Xianhui Feng; Huilin Liu; Peitao Wang; Shichao Zhang; Quanqi Zhu; Chun'an Tang; Yaxing Leng (Journal of Rock Mechanics and Geotechnical Engineering)
Layered rock formations are frequently encountered during the excavation of underground structures. The stability of such structures is influenced not only by the stress concentration caused by the cavities in the strata but also by the anisotropy of the layered rock mass. The interaction between them can lead to critical structural failure, such as rupture, collapse, or significant deformation within the adjacent rock mass, thereby jeopardizing operational safety. However, the coupling law and mechanism between the stress concentration resulting from the cavities and the anisotropy of a layered rock mass remain unclear. In this study, a uniaxial compression test was performed on shale specimens containing a circular hole to investigate the effects of layer inclination and circular holes on the mechanical properties, elastic energy storage, and failure behaviors of these specimens. The failure mechanism of the rock surrounding the hole was analyzed on the basis of the single plane of weakness theory and the Kirsch solution. The test results indicated pronounced anisotropy in the compressive strength, elastic modulus, and elastic strain energy of the specimens, with distinct “V”, “M” and “U”-shaped patterns correlated with varying layer inclination angles. In addition, the combined effect of stress concentration and layer inclination resulted in different failure types, which were classified into four groups according to their failure behavior. Theoretical analysis revealed that failure around circular holes in layered rock is affected by a range of variables, such as layer inclination, layer strength, lateral pressure coefficient, azimuth, and loading stress.